2020
DOI: 10.1177/0269881119895534
|View full text |Cite
|
Sign up to set email alerts
|

Drugs used to treat bipolar disorder act via microRNAs to regulate expression of genes involved in neurite outgrowth

Abstract: Background: The drugs commonly used to treat bipolar disorder have limited efficacy and drug discovery is hampered by the paucity of knowledge of the pathophysiology of this disease. This study aims to explore the role of microRNAs in bipolar disorder and understand the molecular mechanisms of action of commonly used bipolar disorder drugs. Methods: The transcriptional effects of bipolar disorder drug combination (lithium, valproate, lamotrigine and quetiapine) in cultured human neuronal cells were studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
(67 reference statements)
0
10
0
1
Order By: Relevance
“…Li has multiple direct and indirect targets, namely in Wnt, phosphatidylinositol and calcium signaling pathways, in mitochondrial functions and in neuronal excitability [ 25 30 ]. The cellular effects of Li are extensive since many of the downstream targets are transcription factors, miRNAs, histone modifications and DNA methylation, all of which multiply the molecular complexity of the treatment [ 31 , 32 ]. One of the most studied Li targets is glycogen synthase kinase 3 beta (GSK-3β), a component of the canonical or Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Li has multiple direct and indirect targets, namely in Wnt, phosphatidylinositol and calcium signaling pathways, in mitochondrial functions and in neuronal excitability [ 25 30 ]. The cellular effects of Li are extensive since many of the downstream targets are transcription factors, miRNAs, histone modifications and DNA methylation, all of which multiply the molecular complexity of the treatment [ 31 , 32 ]. One of the most studied Li targets is glycogen synthase kinase 3 beta (GSK-3β), a component of the canonical or Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a combination of drugs including lithium, valproate, lamotrigine and quetiapine has been shown to alter the expression of several genes including miRNAs in cultured human neurons. Among the differentially expressed genes have been miR-128 and miR-378 whose targets are enriched in neuron projection development and axonogenesis [ 53 ]. Thus, ncRNAs not only are involved in the pathogenesis of BD but also they might participate in the determination of response to prescribed drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to novel mechanisms, it has been shown how miRNAs play an important role in neurogenesis and synaptogenesis [ 116 , 117 ], and that the expression of several miRNAs are changed in humans and rats by common mood stabilizers, including lithium [ 118 , 119 ]. For example, Chen et al [ 119 ] showed that lithium increased the expression of four miRNAs (miR-34a, miR-152, miR-155 and miR-221) in lymphoblastoid cell lines derived from BD patients, while another study found that mood stabilizers tend to increase the expression of miR-128 and miR-378, which are involved in neuron maturation and synaptogenesis [ 120 ].…”
Section: Pharmacological Treatments and Ahn In Animal Models And Humansmentioning
confidence: 99%